2021
DOI: 10.1145/3474553
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Effectiveness of Web Application Vulnerability Detection Approaches: A Review

Abstract: Most existing surveys and reviews on web application vulnerability detection (WAVD) approaches focus on comparing and summarizing the approaches’ technical details. Although some studies have analyzed the efficiency and effectiveness of specific methods, there is a lack of a comprehensive and systematic analysis of the efficiency and effectiveness of various WAVD approaches. We conducted a systematic literature review (SLR) of WAVD approaches and analyzed their efficiency and effectiveness. We identified 105 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 119 publications
(278 reference statements)
0
0
0
Order By: Relevance
“…Source code review plays a crucial role in detecting security flaws in software systems including BAC vulnerabilities. Studies (e.g., [20]- [22]) found that source code review while utilizing automated source code review tools can effectively detect multiple security issues categories including broken access control. These studies emphasize the importance of incorporating source code review into the software development life cycle to improve the security of the application and strengthen it against potential exploitations.…”
Section: Countermeasures Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Source code review plays a crucial role in detecting security flaws in software systems including BAC vulnerabilities. Studies (e.g., [20]- [22]) found that source code review while utilizing automated source code review tools can effectively detect multiple security issues categories including broken access control. These studies emphasize the importance of incorporating source code review into the software development life cycle to improve the security of the application and strengthen it against potential exploitations.…”
Section: Countermeasures Familiesmentioning
confidence: 99%
“…Security testing is one of the most effective and practical techniques for identifying vulnerabilities in software solutions including broken access control vulnerabilities. Studies (e.g., in [22]- [27]) found that security testing can effectively find BAC vulnerabilities as it analyzes the behavior of the running system and evaluates the implementation of access control policies and applied controls and security levels. Other studies [28] discussed the use of security testing in combination with code review alongside threat modeling to identify BAC vulnerabilities in web applications; nevertheless, studies emphasize the value of the usage of automated security testing tools for effective and automated detection of broken access control vulnerabilities as it can provide a thorough assessment and analysis of the target application and help identify issues that may be overlooked by manual testing.…”
Section: Countermeasures Familiesmentioning
confidence: 99%
“…With the development of machine learning, it has also provided a new approach to SQL injection attack detection [8] . Joshi et al [9] proposed a SQL injection attack detection method that combines the naive Bayes algorithm with role-based access permissions.…”
Section: Related Workmentioning
confidence: 99%
“…Pendekatan metode aplikasi pemindai kerentanan diklasifikasikan ke dalam analisis statis, analisis dinamis, white box, black box, taint analysis, pengujian penetrasi, pengujian fuzz, pengujian concolic, pengujian eksekusi simbolik, dan pemeriksaan model, sebagian besar diklasifikasikan pada pendekatan ke dalam tiga kategori, yaitu, statis, dinamis, dan hybrid [16]. Namun secara keseluruhan, pendekatan tersebut tidak lepas dari artefak (misalnya, Tag HTML, fungsi logika, variabel dalam kode sumber, permintaan HTTP, parameter GET/POST, dan nilai session atau cookie).…”
Section: Modifikasi Web Application Firewallunclassified